ANALISIS RETORIKA SEMITIK ALKITABIAH : Satu Upaya Hermeneutika Lintas Iman & Lintas Tekstual - Solichin, Vitus Rubianto (LOGOS, 2021)
Hermeneutical awareness in the biblical study is very important to underline in order to have a solid formation amidst the various approaches and methodological choices. This paper intends to present a method of interpretation which tends to be open and dialogical, which can be developed for studying other classical religious texts, perhaps even philosophical texts. The Rhetorical Analysis founded at Gregorian University at Rome, Italy, as a new method to understanding the bible can apparently be offered as a model of a cross-cultural hermeneutic that is across disciplines, and even inter-faiths. This rhetorical analysis is called â€œbiblicalâ€ because it focuses on the specific characteristics of the biblical literary tradition itself. Rooted in Semitic culture, this tradition exhibits a marked tendency towards symmetrical and parallel compositions. This rhetorical method is called â€œsemiticâ€ to distinguish it from the classical one, which was developed in the Greco-Roman culture and which is often considered the only rhetoric in the world. The study of the various forms of parallelism and other rules that characterize the composition of the Semitic style helps us to determine the structure of the text more precisely, and thus of course leads to a more adequate understanding of the message it contains.